2016
DOI: 10.1148/radiol.2015142173
|View full text |Cite
|
Sign up to set email alerts
|

Grading of Gliomas by Using Monoexponential, Biexponential, and Stretched Exponential Diffusion-weighted MR Imaging and Diffusion Kurtosis MR Imaging

Abstract: ).q RSNA, 2015 Purpose:To quantitatively compare the potential of various diffusion parameters obtained from monoexponential, biexponential, and stretched exponential diffusion-weighted imaging models and diffusion kurtosis imaging in the grading of gliomas. Materials andMethods:This study was approved by the local ethics committee, and written informed consent was obtained from all subjects. Both diffusion-weighted imaging and diffusion kurtosis imaging were performed in 69 patients with pathologically pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
169
4

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(193 citation statements)
references
References 35 publications
20
169
4
Order By: Relevance
“…Advanced fitting models for DWI were recently described [7][8][9][10][11][12][13]. For example, a model using intravoxel incoherent motion (IVIM) was proposed; by using the bi-exponential decay function, it divides the fast and slow diffusion components, which reflects the true tissue diffusivity and capillary perfusion, respectively [7,8].…”
Section: Diffusion-weighted Imaging (Dwi) Is a Well-known Noninvasivementioning
confidence: 99%
See 2 more Smart Citations
“…Advanced fitting models for DWI were recently described [7][8][9][10][11][12][13]. For example, a model using intravoxel incoherent motion (IVIM) was proposed; by using the bi-exponential decay function, it divides the fast and slow diffusion components, which reflects the true tissue diffusivity and capillary perfusion, respectively [7,8].…”
Section: Diffusion-weighted Imaging (Dwi) Is a Well-known Noninvasivementioning
confidence: 99%
“…A stretched exponential model (SEM) diffusion model was described as follows: the SEM model was used to describe the heterogeneity of water diffusion in each voxel. In this model, to obtain a good fit to multiple b-value signal decay data, the two parameters of diffusion heterogeneity and diffusion coefficient are respectively calculated [11,12]. A diffusion kurtosis imaging (DKI) model also uses the diffusion distribution information.…”
Section: Diffusion-weighted Imaging (Dwi) Is a Well-known Noninvasivementioning
confidence: 99%
See 1 more Smart Citation
“…However, the ADC values do not accurately indicate pure water diffusion in the tissue and tend to be overestimated because they are contaminated by perfusion most apparent in low b-values (e.g., < 100–150 s/mm 2 ). Recent studies reported that ADC ratios, histogram analysis, and diffusion kurtosis based on non-Gaussian water diffusion might better characterize high-grade brain tumors (3141516). Furthermore, a diffusion heterogeneity index calculated from a stretched exponential model or a fractional order calculus model with multi-b-value DWI recently demonstrates improved tumor grading in adult gliomas (16) and pediatric brain tumors (17).…”
Section: Diffusion-weighted Imagingmentioning
confidence: 99%
“…Several of these DKI metrics have been shown to detect subtle changes in brain tissue structure. To briefly summarize, studies have shown DKI to have potential in diagnostics of a number of diseases such as stroke [4,5], Alzheimer's disease [6], multiple sclerosis [7], gliomas [8,9], and head trauma [10][11][12] (see also the review of this area in Ostergaard et al [13]). DKI is not only of clinical interest but is also a valuable tool in basic neuroscience, and the method has for example been employed in studies of natural alteration of brain microstructure e.g., in the context of development and aging [14,15].…”
Section: Introductionmentioning
confidence: 99%